Electrode assembly including adhesive insulating coating parts and electrochemical device including the same

KR103019792B1Active Publication Date: 2026-09-15LG ENERGY SOLUTION LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
KR1020240065869
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-26
Filing Date
2024-05-21
Publication Date
2026-09-15
Estimated Expiration
2044-05-21

Smart Images

  • Figure 112024054840461-PAT00001_ABST
    Figure 112024054840461-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to an electrode assembly that improves adhesion between an anode and a separator by imparting adhesion to an insulating coating portion, and a composition for insulating coating thereto. An electrode assembly according to one aspect of the present invention has the advantage of improving the safety of an electrochemical device by improving the phenomenon of the separator folding due to excellent wet adhesion between the electrode and the separator.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an electrode assembly comprising an insulating coating portion and an electrochemical device comprising the same. Background Technology

[0002] With the increasing technological development and demand for mobile devices, the demand for secondary batteries as an energy source is rapidly rising. Recently, the use of secondary batteries as power sources for electric vehicles (EVs) and hybrid electric vehicles (HEVs) has become a reality. Accordingly, extensive research is being conducted on secondary batteries capable of meeting various requirements.

[0003] In particular, there is high demand for lithium-ion batteries that possess high energy density, high discharge voltage, and output stability. Among these, lithium-ion batteries used as power sources for electric and hybrid electric vehicles require high-output characteristics capable of delivering large output in a short period of time. Consequently, there is continuing interest in improving battery safety for use in such lithium-ion batteries.

[0004] Meanwhile, secondary batteries can be classified into jelly-roll (wound type) electrode assemblies, stack type (laminated type) electrode assemblies, and stack / folding type electrode assemblies depending on the structure in which the electrode assembly is formed, and basically, the electrode assembly includes three elements as basic components: a positive electrode, a separator, and a negative electrode.

[0005] A conventional electrode assembly has a stacked structure in which a separator is interposed between an anode and a cathode, with an electrode tab protruding from one side. However, in this structure, if the temperature rises due to exposure to an external heat source or an internal short circuit, causing the separator to shrink, there is a problem in which parts of the anode and cathode come into contact, thereby inducing a short circuit.

[0006] Consequently, research is being conducted to solve the aforementioned problems by utilizing insulating materials, such as by inserting an insulating layer into a part of the electrode assembly. For example, research is underway to prevent short circuits, lithium deposition, and ignition by providing an insulating layer using PVDF-based resin on the anode.

[0007] However, problems have been reported with PVDF-based insulating materials currently under research and development, such as detachment due to insufficient adhesion or dissolution by the electrolyte when injected into the electrode assembly. Furthermore, short-circuit phenomena are still being reported, where the adhesion between the components of the electrode assembly is reduced and the separator folds instead of adhering to the electrode, causing parts of the anode and cathode to come into contact. The problem to be solved

[0008] Therefore, the present invention solves the above-mentioned problem, and

[0009] The present invention aims to provide an electrode assembly that effectively solves the short-circuit problem between the anode and the cathode, and an electrochemical device including the same.

[0010] In particular, the electrode assembly of the present invention includes an insulating coating portion and aims to provide an electrode assembly having excellent adhesion between the electrode and the separator.

[0011] For example, the electrode assembly of the present invention includes an insulating coating portion, and aims to provide an electrode assembly with excellent adhesion between the anode and the separator. means of solving the problem

[0012] In order to solve the above problem,

[0013] According to one aspect of the present invention, electrode assemblies of the following embodiments are provided.

[0014] The electrode assembly according to the first embodiment is,

[0015] An electrode assembly comprising an anode, a cathode, and a separator interposed between the anode and the cathode,

[0016] At least one of the anode and the cathode comprises: a current collector; an active material layer formed on at least one surface of the current collector; and an insulating coating portion formed around the entire outer periphery of one surface of the active material layer.

[0017] The wet adhesion between the anode or cathode equipped with the insulating coating and the separator is 1 to 20 gf / 20 mm.

[0018] According to the second embodiment, in the first embodiment,

[0019] At least one of the anode and the cathode may each include an active material layer on both sides of the current collector; and an insulating coating portion formed around the entire outer periphery of one side of each of the active material layers.

[0020] According to the third embodiment, in the first embodiment or the second embodiment,

[0021] The above insulating coating part comprises inorganic particles and a binder, and

[0022] The above binder may include two types of adhesive binders having a difference in glass transition temperature (Tg) of 100°C or less.

[0023] According to the fourth embodiment, in any one of the first to third embodiments,

[0024] The above insulating coating part comprises inorganic particles and a binder, and

[0025] The above binder may include a first adhesive binder having a glass transition temperature (Tg) of 50°C or higher, and a second adhesive binder having a glass transition temperature (Tg) of 20°C or lower.

[0027] According to another aspect of the present invention, an insulating coating composition of the following embodiments is provided.

[0028] The insulating coating composition according to the fifth embodiment is,

[0029] It includes inorganic particles and a binder,

[0030] The above binder may include two types of adhesive binders having a difference in glass transition temperature (Tg) of 100°C or less.

[0031] The insulating coating composition according to the 6th embodiment is,

[0032] It includes inorganic particles and a binder,

[0033] The above binder may include a first adhesive binder having a glass transition temperature (Tg) of 50°C or higher, and a second adhesive binder having a glass transition temperature (Tg) of 20°C or lower.

[0034] According to the seventh embodiment, in the sixth embodiment,

[0035] The first adhesive binder above may include a water-based particulate binder.

[0036] According to the eighth embodiment, in the sixth or seventh embodiment,

[0037] The first adhesive binder above may include a water-based particulate binder having a particle size of 250 nm or more.

[0038] According to the ninth embodiment, in any one of the sixth to eighth embodiments,

[0039] The second adhesive binder may include a water-based particle binder, a solution-based binder, or a mixture thereof.

[0040] According to the 10th embodiment, in any one of the 6th to 9th embodiments,

[0041] The second adhesive binder above may include a water-based particulate binder having a particle size of 250 nm or less.

[0042] According to the 11th embodiment, in any one of the 6th to 10th embodiments,

[0043] The weight ratio of the first adhesive binder and the second adhesive binder may be 1:9 to 9:1.

[0044] According to the 12th embodiment, in any one of the 5th to 11th embodiments,

[0045] The weight ratio of the inorganic particles and the binder may be 7:3 to 9:1.

[0047] According to another aspect of the present invention, electrochemical elements of the following embodiments are provided.

[0048] The electrochemical device according to the 13th embodiment is,

[0049] An electrode assembly according to any one of the first to fourth embodiments may be housed in a case.

[0051] According to another aspect of the present invention, a method for manufacturing an electrode assembly of the following embodiments is provided.

[0052] The method for manufacturing an electrode assembly according to the 14th embodiment is,

[0053] A step of preparing a current collector and an electrode having an active material layer on at least one surface of the current collector,

[0054] A step of forming an insulating coating portion comprising inorganic particles and a binder over the entire outer periphery of one surface of the active material layer, and

[0055] The method includes the step of rolling after contacting a separator membrane to the surface on which the insulating coating portion is formed.

[0056] The above electrode is at least one of a positive electrode and a negative electrode, and

[0057] The wet adhesion between the electrode formed with the insulating coating and the separator may be 1 to 20 gf / 20 mm. Effects of the invention

[0058] An electrode assembly according to one embodiment of the present invention can increase the adhesion between the electrode and the separator and suppress the occurrence of a short circuit between the electrodes by providing an adhesive insulating coating portion around the outer periphery of the electrode.

[0059] Thus, the risk of explosion and fire caused by the above paragraph can be reduced, thereby having a favorable effect on improving safety. Brief explanation of the drawing

[0060] FIG. 1 illustrates an embodiment according to the present invention in which an electrode active material layer (11) is formed on a current collector having a tab portion (1) formed thereon, and an insulating coating portion (20) is formed around the entire outer periphery of one surface of the electrode active material layer. FIG. 2 is a side view of one embodiment of an assembly in which an electrode active material layer (11), an insulating coating part (20), and a separator (30) are sequentially stacked on a current collector (10) having a tab part (1) formed thereon according to one embodiment of the present invention. FIG. 3 is a vertical cross-sectional view of the central portion of an assembly in which an electrode active material layer (11), an insulating coating portion (20), and a separator (30) are sequentially stacked on a current collector (10) having a tab portion (1) formed thereon according to one embodiment of the present invention. Specific details for implementing the invention

[0061] The present invention will be described in detail below.

[0062] In this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0063] In this specification, the description of the term "A and / or B" means "A or B, or both."

[0064] The present invention relates to an electrode assembly and an electrochemical device including the same. Examples of the electrochemical device include a primary battery, a secondary battery, a supercapacitor, an electric double layer capacitor, etc. More specifically, the secondary battery may be a lithium-ion secondary battery.

[0066] The electrode assembly and electrochemical element of the present invention will be described in more detail below with reference to the drawings.

[0067] An electrode assembly according to one aspect of the present invention has a structure comprising an anode, a cathode, and a separator interposed between the anode and the cathode. At this time, at least one of the anode and the cathode comprises a current collector; an active material layer formed on at least one surface of the current collector; and an insulating coating portion formed around the entire outer periphery of one surface of the active material layer, wherein the wet adhesion strength between the anode or cathode equipped with the insulating coating portion and the separator is 1 to 20 gf / 20 mm.

[0068] In one embodiment of the present invention, the anode comprises an active material layer formed on at least one surface and an insulating coating portion formed around the entire outer periphery of one surface of the active material layer, and the wet adhesion strength between the one surface of the anode equipped with the insulating coating portion and the separator may be 1 to 20 gf / 20 mm.

[0069] In another embodiment of the present invention, the active material layer formed on at least one surface of the cathode and the insulating coating portion formed around the entire outer periphery of one surface of the active material layer are included, and the wet adhesion strength between the one surface of the cathode equipped with the insulating coating portion and the separator may be 1 to 20 gf / 20 mm.

[0070] In another embodiment of the present invention, the anode and the cathode each comprise an active material layer formed on at least one surface and an insulating coating portion formed around the entire outer periphery of one surface of the active material layer, and the wet adhesion force between one surface of the anode equipped with the insulating coating portion and the separator and / or the wet adhesion force between one surface of the cathode equipped with the insulating coating portion and the separator may be 1 to 20 gf / 20 mm.

[0071] FIG. 1 illustrates a schematic diagram of an example of the electrode. Specifically, FIG. 1 illustrates an embodiment in which an electrode active material layer (11) is formed on a current collector having a tab portion (1) formed thereon according to one embodiment of the present invention, and an insulating coating portion (20) is formed around the entire outer periphery of one surface of the electrode active material layer.

[0072] Referring to FIG. 1, in one embodiment of the present invention, the electrode may have a structure comprising a current collector, an active material layer (11) formed on at least one surface of the current collector, and an electrode tab (1) extending from the current collector. At this time, the insulating coating portion (20) is formed to surround the entire outer perimeter of one surface of the active material layer (11).

[0073] FIG. 2 illustrates a schematic diagram of one embodiment in which the electrode and separator are attached. Specifically, FIG. 2 shows that, according to one embodiment of the present invention, the electrode active material layer (11) formed on the current collector (10) having a tab portion (1) includes an insulating coating portion (20) around the outer periphery, so that the insulating coating portion (20) can be positioned between the electrode active material layer (11) and the separator (30). Accordingly, the adhesion between the electrode active material layer and the separator can be improved, and the effect of improving the folding phenomenon of the separator during the manufacture of the electrode assembly can be achieved.

[0074] In one embodiment of the present invention, the electrode may have an active material layer on each of the two sides of the current collector, and may include an insulating coating portion formed around the entire outer periphery on one side of each of the active material layers. In this case, the electrode may be a positive electrode and / or a negative electrode, but the present invention is not limited thereto.

[0075] FIG. 3 illustrates a schematic diagram of one embodiment in which the electrode and separator are attached. Specifically, FIG. 3 shows a vertical cross-sectional view centered on the central part of the assembly to which the electrode and separator are attached. Referring to FIG. 3, since the insulating coating portion (20) is formed around the outer periphery of the electrode active material layer (11), the insulating coating portion is not included on the inner surface area of ​​the electrode active material layer (11). At this time, in order to prevent the phenomenon in which the electrode active material layer and the separator do not adhere due to the thickness of the insulating coating portion itself, it is preferable that the insulating coating portion be formed thinly so that when pressure is applied between the electrode and the separator during the manufacture of the electrode assembly, one side of the electrode active material layer can sufficiently contact the separator.

[0076] In one embodiment of the present invention, the insulating coating portion is formed to surround the entire outer periphery of one surface of the electrode active material layer and may be formed to have a thickness of, for example, 0.5 to 1 μm. In the manufacture of conventional electrode assemblies, the electrode active material layer may exhibit a thickness variation of, for example, about 3 μm or more due to sliding phenomena of the electrode slurry. However, according to the present invention, by forming a thin insulating coating portion as described above around the outer periphery of the electrode active material layer, not only can the thickness variation of the entire electrode be improved, but the adhesion between the electrode and the separator can also be improved to reduce the folding phenomenon of the separator, thereby improving the safety of the battery. However, the mechanism of the present invention is not limited thereto.

[0077] In one embodiment of the present invention, the insulating coating portion formed over the entire outer periphery of one surface of the electrode active material layer may have an area of, for example, 5% to 50%, 10% to 30%, or 15% to 20% based on the total area of ​​one surface of the electrode active material layer. While it may be desirable in terms of the energy density of the electrode while maintaining the effect of the insulating coating portion when the insulating coating portion has an area within the above-described range based on the area of ​​one surface of the electrode active material layer, the present invention is not limited thereto.

[0078] In one embodiment of the present invention, the area of ​​the insulating coating portion can be measured by obtaining an image of the upper surface of the electrode on which the insulating coating portion is formed, when the direction in which the current collector, the electrode active material layer, and the insulating coating portion are stacked is the up-down direction, and then measuring the area occupied by the insulating coating portion relative to the total area of ​​the active material layer. At this time, the image of the upper surface of the electrode is not particularly limited, such as a photographic image or a microscopic image such as an SEM.

[0079] The above electrode assembly exhibits a wet adhesion force of 1 to 20 gf / 20 mm at the interface between the electrode equipped with the insulating coating and the separator, thereby improving the phenomenon where the separator does not adhere to the electrode within the electrode assembly and folds, and thus can exhibit an excellent effect of preventing short circuits between the electrodes.

[0080] In this specification, the wet adhesion refers to the adhesion measured in the presence of an electrolyte in an environment similar to the environment in which the electrode assembly operates as a battery. Even when the dry adhesion between an electrode, such as a positive or negative electrode, and a separator is high, there may be a problem in which the wet adhesion is not sufficiently secured when the electrode assembly comes into contact with an electrolyte and each component of the electrode assembly is wet by the electrolyte, such as due to a decrease in frictional force between the components or the dissolution of adhesive components. To solve this problem, according to one aspect of the present invention, an electrode assembly is provided in which the wet adhesion between one surface of the electrode equipped with the insulating coating and the separator is secured in the range of 1 to 20 gf / 20 mm.

[0081] In one embodiment of the present invention, the wet adhesion force between the electrode and the separator may be, for example, 5 to 15 gf / 20 mm or 8 to 12 gf / mm. For example, the wet adhesion force between the electrode and the separator may be 10 gf / mm, but the present invention is not limited thereto. When the wet adhesion force between the electrode and the separator is within the range described above, it may exhibit an advantageous effect in terms of maintaining the adhesion force of the separator even after the electrolyte is injected into the electrode assembly.

[0082] In this specification, the wet adhesion strength may be measured, for example, by the following method, but is not limited thereto. First, an electrode and a separator, each having an insulating coating formed around the entire outer perimeter of one side of the active material layer, are cut into samples of 25 mm x 60 mm size, and then an electrode-separator sample is prepared by applying pressure of 6.5 MPa at 60°C for 1 second using a heat press. Subsequently, the electrode-separator sample is placed in a pouch, 1 g of electrolyte is injected, and the sample is impregnated for 1 day. Then, the electrode-separator sample is removed from the pouch, mounted on a UTM device (LLOYD Instrument LF Plus), and the 90° peel strength is measured at a speed of 300 mm / min.

[0083] In one embodiment of the present invention, the electrode assembly may be characterized by having excellent wet adhesion between the electrode and the separator as well as dry adhesion.

[0084] In one embodiment of the present invention, the dry adhesion force between the electrode and the separator may be, for example, 5 to 30 gf / 25 mm, 10 to 28 gf / 25 mm, 15 to 25 gf / 25 mm, or 18 to 23 gf / 25 mm. For example, the dry adhesion force between the electrode and the separator may be 20 gf / 25 mm.

[0085] In this specification, the dry adhesion strength may be measured, for example, by the following method, but is not limited thereto. After obtaining samples of an electrode and a separator, each having an insulating coating formed around the entire outer periphery of the active material layer, cut to a size of 25 mm x 60 mm, an electrode-separator sample is prepared by applying pressure of 6.5 MPa at 60°C for 1 second using a heat press. Subsequently, the electrode-separator sample is mounted on a UTM instrument (LLOYD Instrument LF Plus), and the 180° peel strength is measured at a speed of 300 mm / min.

[0086] In one embodiment of the present invention, the electrode assembly may be characterized by having excellent peel strength between the active material layer and the insulating coating portion.

[0087] In this specification, the peel strength refers to the adhesion strength between the insulating coating portion formed on the entire outer periphery of the active material layer and the active material layer.

[0088] In one embodiment of the present invention, the peel strength between the active material layer and the insulating coating portion may be, for example, 5 to 30 gf / 15mm, 10 to 30 gf / 15mm, 15 to 25 gf / 15mm, or 20 to 25 gf / 15mm. For example, the peel strength between the active material layer and the insulating coating portion may be 20 gf / 15mm.

[0089] In this specification, the peel strength may be measured in the following manner, for example, but is not limited thereto. The anode to be measured is cut to a size of 15 mm x 100 mm. Double-sided adhesive tape is attached to a glass plate, and the surface of the insulating coating portion and the active material layer of the prepared electrode is attached to the adhesive tape. Afterward, the end portion of the attached insulating coating portion is mounted on a UTM device (LLOYD Instrument LF Plus), and a force is applied at a measurement speed of 300 mm / min at 180° to measure the force required to peel off the insulating coating portion and the active material layer.

[0090] According to one embodiment of the present invention, the insulating coating portion comprises inorganic particles and a binder. In this case, to exhibit the adhesive strength described above, the binder comprises an adhesive binder.

[0091] In one embodiment of the present invention, the binder included in the insulating coating portion may include two types of binders having different glass transition temperatures (Tg) as adhesive binders.

[0093] Hereinafter, a composition for insulating coating according to another aspect of the present invention will be described in detail.

[0094] According to another aspect of the present invention, a composition for insulating coating is provided.

[0095] The above insulating coating composition can be used to form an insulating coating portion formed on an electrode within the electrode assembly described above.

[0096] The above insulating coating composition comprises inorganic particles and a binder, wherein the binder comprises a first adhesive binder having a glass transition temperature (Tg) of 50°C or higher and a second adhesive binder having a glass transition temperature (Tg) of 20°C or lower.

[0097] According to one aspect of the present invention, the insulating coating composition includes an adhesive binder, thereby exhibiting the effect of improving adhesion between the anode and the separator. In this case, by including two types of adhesive binders with different glass transition temperature ranges, the binder can exhibit excellent wet adhesion and dry adhesion, as well as excellent peel strength between the active material layer and the insulating coating portion.

[0098] Specifically, the two types of adhesive binders included in the insulating coating composition may be named, in order, the first adhesive binder and the second adhesive binder. The first adhesive binder and the second adhesive binder can function to stably maintain the insulating performance of the insulating coating by binding inorganic particles together within the insulating coating.

[0099] In one embodiment of the present invention, the first adhesive binder may additionally perform the function of improving the adhesion between the insulating coating part and the separator, specifically the adhesion between the anode and the separator, although the function is not limited thereto. Additionally, the second adhesive binder may additionally perform the function of improving the adhesion between the insulating coating part and the active material and / or the current collector, although the function is not limited thereto. For the purpose of improving the adhesion between the anode and the separator and improving the adhesion between the active material layer and the insulating coating part as described above, the binder may comprise two types of binders having different glass transition temperatures, but the effects of the present invention are not limited thereto.

[0100] In this specification, the glass transition temperature (Tg) indicates the temperature range in which the glass transition of the binder occurs. The glass transition temperature may be measured according to known methods for measuring glass transition temperatures, such as differential scanning calorimeter (DSC), specific heat measurements, dilatometer, thermomechanical analysis (DMA), thermal expansion measurement (TAM), micro-heat-transfer measurement, isothermal compressibility, and heat capacity measurement.

[0101] In this specification, the glass transition temperature value may represent a value measured by a method of measuring the heat flow within a binder sample during a linear temperature rise process, particularly using a differential scanning calorimeter (DSC), and it will be obvious to a person skilled in the art that the numerical value of the glass transition temperature includes a measurement error range of a predetermined range based on the stated value, for example, a measurement error range of -5% to +5%.

[0102] In one embodiment of the present invention, the binder may comprise two types of adhesive binders having a difference in glass transition temperature (Tg) of 100°C or less. Specifically, the binder may comprise two types of adhesive binders having a difference in glass transition temperature of 90°C or less. More specifically, the binder may comprise two types of adhesive binders having a difference in glass transition temperature of, for example, 50°C to 90°C, 60°C to 80°C, 65°C to 75°C, or 65°C to 70°C.

[0103] In one embodiment of the present invention, the glass transition temperature of the first adhesive binder may be, for example, 50°C to 80°C or 50°C to 70°C.

[0104] In one embodiment of the present invention, the glass transition temperature of the second adhesive binder may be, for example, -50°C to 20°C, -40°C to 0°C, or -30°C to -10°C.

[0105] In one embodiment of the present invention, the first adhesive binder may be a water-based particulate binder having a glass transition temperature of 50°C or higher.

[0106] In this specification, the term "aqueous particulate binder" refers collectively to binders that are dispersed in an aqueous solvent, such as water (H2O), and exhibit a particulate shape. The type of particulate binder is not particularly limited as long as it satisfies the characteristics described above, but it may be, for example, an acryl-based polymer, a rubber-based polymer, a cellulose-based polymer, or a mixture thereof. The acryl-based polymer may include, for example, polyalkyl (meth)acrylates, and the "alkyl" may be a C1 to C5 alkyl, but is not particularly limited. The rubber-based polymer may be a rubber-based polymer containing at least one butadiene unit, and examples include polybutadiene rubber, styrene-butadiene rubber, nitrile butadiene rubber, but are not limited thereto. The above-mentioned cellulose-based polymers collectively refer to cellulose and derivatives of cellulose, and examples include, but are not limited to, cellulose, carboxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose phthalate.

[0107] In one embodiment of the present invention, the first adhesive binder may include a water-based particle binder, and specifically, may be composed solely of a water-based particle binder. In this case, the water-based particle binder of the first adhesive binder may include particles with a larger particle size than the inorganic particles included in the insulating coating composition, as described below.

[0108] Specifically, the first adhesive binder may be a water-based particle type binder, and it may be preferable that it be larger in size than the inorganic particles of the insulating coating composition so that it is not soaked between the inorganic particles within the insulating coating but exists on the surface of the insulating coating, thereby exhibiting excellent adhesion to the separator.

[0109] In one embodiment of the present invention, the first adhesive binder may be a water-based particle binder having a particle size of 250 nm or more. The first adhesive binder may be a water-based particle binder having, for example, a particle size of 250 nm to 1 μm or 250 nm or 500 nm, but is not limited thereto.

[0110] In this specification, the particle size of the particulate binder may be a value measured through the particle size distribution (PSD) analysis method, for example, a value measured using the Malvern Mastersizer 2000.

[0111] In one embodiment of the present invention, the second adhesive binder can improve the bonding strength between inorganic particles within the insulating coating portion and, by soaking between the inorganic particles, improve the adhesion strength between the active material layer and / or the positive current collector and the insulating coating portion.

[0112] To this end, in one embodiment of the present invention, the second adhesive binder may comprise a water-based particle binder, a solution-based binder, or a mixture thereof. Alternatively, the second adhesive binder may consist solely of a water-based particle binder or a solution-based binder, respectively.

[0113] In one embodiment of the present invention, when the second adhesive binder comprises a water-based particle binder, it may be preferable that the water-based particle binder comprises a particle of the same size as or smaller than the inorganic particle so that it can be impregnated between the inorganic particles within the insulating coating portion.

[0114] In one embodiment of the present invention, the second adhesive binder may be a water-based particle binder having a particle size of 250 nm or less. The second adhesive binder may be a water-based particle binder having, for example, a particle size of 50 nm to 250 nm or 100 nm to 200 nm, but is not limited thereto.

[0115] In one embodiment of the present invention, the second adhesive binder may include a solution-type binder.

[0116] In this specification, the term "solution-type binder" refers collectively to binders that are soluble in polar solvents including water (H2O), and may also be referred to as "dissolvable binders." The type of solution-type binder is not particularly limited as long as it satisfies the characteristics described above, but may include, for example, PVDF-based polymers, polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyacrylamide (PAM), or a mixture of two or more of these. The PVDF-based polymer is a collective term for polymers containing vinylidene fluoride as a monomer, such as polyvinylidene fluoride (PVDF) and polyvinylidene-co-hexafluoropropylene.

[0117] In one embodiment of the present invention, the adhesive strength described above is not particularly limited as long as it can exhibit such strength, but for example, the weight ratio of the first adhesive binder and the second adhesive binder may be 1:9 to 9:1. Specifically, the weight ratio of the first adhesive binder and the second adhesive binder may be 5:5 to 8:2.

[0118] In one embodiment of the present invention, the inorganic particles may be used without particular limitation as long as they can be used in the insulating coating portion of an electrode. The inorganic particles may be, for example, alumina (Al2O3), boehmite (AlOOH), silica (SiO2), titanium dioxide (TiO2), aluminum hydroxide (Al(OH)3), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), zinc oxide (ZnO), barium titanate (BaTiO), aluminum nitride (ANN), boron nitride (BN), silicon carbide (SiC), beryllium oxide (BeO), potassium nitrate (KNO3), ammonium dihydrogen phosphate (NH4H2PO4), or a mixture of two or more of these, but are not limited thereto. Specifically, the inorganic particles may include alumina (Al2O3), boehmite (AlOOH), silica (SiO2), or a mixture of two or more of these.

[0119] In one embodiment of the present invention, the inorganic particles may have, for example, an average particle size of 250 nm or more. Specifically, the average particle size of the inorganic particles may be 250 nm to 1,000 µm or 250 nm to 500 µm.

[0120] In this specification, the 'average particle size' is D 50 It may indicate the average particle size. The above ' D 50 'Average particle size' refers to the particle size at the 50% point of the cumulative distribution of particle volume according to particle size. The above D 50The average particle size can be measured using the laser diffraction method. Specifically, the particles to be measured are dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size measuring device. The particle size distribution can be calculated and measured by measuring the difference in diffraction patterns according to particle size as the particles pass through a laser beam. The commercially available laser diffraction particle size measuring device may be, for example, Microtrac's S3500, but is not limited thereto.

[0121] In one embodiment of the present invention, the weight ratio of the inorganic particles and the binder is not particularly limited in such a way as not to impede the purpose of the present invention, but may be, for example, 9:1 to 1:9. Specifically, the weight ratio of the inorganic particles and the binder may be 7:3 to 9:1, more specifically 8:2. When the weight ratio of the inorganic particles and the binder is within the range described above, advantageous effects may be exhibited in terms of the insulating properties of the insulating coating part, the adhesion of the anode, and the adhesion of the insulating coating part, but the present invention is not limited thereto.

[0123] Hereinafter, other configurations of an electrode assembly according to one aspect of the present invention will be described in detail.

[0124] anode

[0125] As described above, the anode comprises a current collector and an active material layer formed on at least one surface of the current collector.

[0126] In one embodiment of the present invention, the anode may include a current collector; an active material layer formed on at least one surface of the current collector; and an insulating coating portion formed around the entire outer periphery of the active material layer.

[0127] The above current collector supports the above active material layer and is not particularly limited as long as it has high conductivity without causing chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, palladium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, silver, etc., and aluminum-cadmium alloy may be used.

[0128] The above current collector can strengthen the bonding force with the positive active material by forming fine irregularities on its surface, and can be used in various forms such as film, sheet, foil, mesh, net, porous body, foam, nonwoven fabric, etc.

[0129] The above active material layer includes a positive active material and may further include a conductive material, a binder, and additives.

[0130] In one embodiment of the present invention, the positive electrode active material may comprise, for example, a lithium transition metal oxide; a lithium metal iron phosphate; a lithium nickel-manganese-cobalt oxide; an oxide in which a portion of the lithium nickel-manganese-cobalt oxide is substituted with another transition metal; or two or more of these, but is not limited thereto. Specifically, the positive electrode active material may comprise, for example, a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; and a compound with the chemical formula Li 1+x Mn 2-x Lithium manganese oxides such as O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, LiMnO2, etc.; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7, etc.; chemical formula LiNi 1-x M x Ni-site type lithium nickel oxide represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B, or Ga, and x = 0.01 ~ 0.3); chemical formula LiMn 2-xM x Lithium manganese composite oxides represented as O2 (where M = Co, Ni, Fe, Cr, Zn, or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu, or Zn); lithium metal phosphate LiMPO4 (where M = Fe, CO, Ni, or Mn); lithium nickel-manganese-cobalt oxide Li 1+x (Ni a Co b Mn c ) 1-x O2(x = 0 ~ 0.03, a = 0.3 ~ 0.95, b = 0.01 ~ 0.35, c = 0.01 ~ 0.5, a+b+c=1); Lithium nickel-manganese-cobalt oxide, a lithium oxide in which a portion is substituted with aluminum Li a [Ni b Co c Mn d Al e ] 1-f M1 f O2(M1 is one or more selected from the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S, and 0.8≤a≤1.2, 0.5≤b≤0.99, 0 <c<0.5, 0<d<0.5, 0.01≤e≤0.1, 0≤f≤0.1); 리튬 니켈-망간-코발트 산화물에 일부가 다른 전이금속으로 치환된 산화물 Li 1+x (Ni a Co b Mn c M d ) 1-x Examples include O2 (x = 0 ~ 0.03, a = 0.3 ~ 0.95, b = 0.01 ~ 0.35, c = 0.01 ~ 0.5, d = 0.001 ~ 0.03, a+b+c+d=1, M is any one selected from the group consisting of Fe, V, Cr, Ti, W, Ta, Mg and Mo), disulfide compounds; Fe2(MoO4)3, etc., but are not limited to these.

[0131] In one embodiment of the present invention, the conductive material is a material that electrically connects the electrolyte and the positive electrode active material and serves as a path for electrons to move from the current collector to the positive electrode active material, and can be used without limitation as long as it has conductivity as an electrode component that is physically distinct from the carbon contained in the sulfur-carbon composite.

[0132] In one embodiment of the present invention, the conductive material may be used alone or in combination with carbon black such as Super-P, Denka Black, Acetylene Black, Ketjen Black, Channel Black, Furnace Black, Lamp Black, Thermo Black, Carbon Black; carbon derivatives such as carbon nanotubes or fullerenes; conductive fibers such as carbon fibers or metal fibers; metal powders such as fluorinated carbon, aluminum, or nickel powder; or conductive polymers such as polyaniline, polythiophene, polyacetylene, or polypyrrole.

[0133] In one embodiment of the present invention, the content of the conductive material may be 0 to 10 weight%, for example, 1 to 10 weight%, with respect to the total weight of the active material layer. If the content of the conductive material is less than the above range, electron transfer between the positive active material and the current collector is not easy, which may result in a decrease in voltage and capacity; conversely, if it exceeds the above range, the relative proportion of the positive active material decreases, which may result in a decrease in the total energy (charge) of the battery. Therefore, it is desirable to determine an appropriate content within the above-described range.

[0134] In one embodiment of the present invention, the positive active material layer comprises a positive active material and a binder polymer, and may not include a conductive material. Since the positive does not include a conductive material, there is an advantage that it can include more positive active material.

[0135] In one embodiment of the present invention, the anode binder maintains the anode active material on the anode current collector and organically connects the anode active materials to further increase the bonding force between them, and any binder polymer known in the industry may be used.

[0136] In one embodiment of the present invention, the binder in the positive active material layer may be the same as or different from the binder of the insulating coating part, i.e., the first adhesive binder and / or the second adhesive binder, and may be selected independently thereof.

[0137] In one embodiment of the present invention, the binder in the positive electrode active material layer comprises, for example, a fluoropolymer-based binder including polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE); a rubber-based binder including styrene butadiene rubber (SBR), acrylonitrile-butidiene rubber, styrene-isoprene rubber; a cellulose-based binder including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose; a polyalcohol-based binder; a polyolefin-based binder including polyethylene, polypropylene, etc.; a polyimide-based binder; a polyester-based binder; a polyacrylic-based binder such as polyacrylic acid (PAA); a silane-based binder; and a polyurethane-based binder. Alternatively, it may include a mixture of two or more of these, and the binder polymer may also include a copolymer having repeating units derived from two or more of these binders.

[0138] In one embodiment of the present invention, the content of the binder polymer may be 0.5 to 30 wt% with respect to the total 100 wt% of the positive electrode active material layer. When the content of the binder polymer satisfies this range, the physical properties of the positive electrode are improved, preventing the phenomenon of the active material and conductive material detaching within the positive electrode, and the ratio of the active material and conductive material in the positive electrode is appropriately controlled so that the battery capacity can be secured.

[0140] cathode

[0141] The above-mentioned cathode may include a cathode current collector and a cathode active material layer coated on one or both sides of the cathode current collector. Alternatively, the above-mentioned cathode may be a lithium metal plate.

[0142] In one embodiment of the present invention, the cathode may include a current collector; an active material layer formed on at least one surface of the current collector; and an insulating coating portion formed around the entire outer periphery of the active material layer.

[0143] The above-mentioned negative current collector is for supporting the negative active material layer and is as described in the positive current collector.

[0144] The above-mentioned negative electrode active material layer may include a conductive material, a binder, etc., in addition to the negative electrode active material. In this case, the conductive material and the binder follow the aforementioned specifications.

[0145] The above negative electrode active material is lithium (Li + It may include a material capable of reversibly intercalating or deintercalating ), a material capable of reacting with lithium ions to reversibly form a lithium-containing compound, a lithium metal, or a lithium alloy.

[0146] The above lithium ion (Li + A material capable of reversibly inserting or deinserting ) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. The lithium ions (Li +A material capable of reversibly forming a lithium-containing compound by reacting with ) may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of a metal selected from the group consisting of lithium (Li) and sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0148] Separator

[0149] The above separator separates or insulates the anode and cathode from each other and enables lithium ion transport between the anode and cathode; it can be used without particular limitation as long as it is typically used in an electrochemical device. For example, the above separator may be provided in a shape such as a film.

[0150] According to one embodiment of the present invention, the separator may comprise a porous substrate and a porous coating layer formed on at least one surface of the porous substrate.

[0151] Hereinafter, the composition of the porous substrate and the porous coating layer is described by example.

[0152] In one embodiment of the present invention, the porous substrate refers to a substrate having a plurality of pores formed therein, which acts as a porous ion-conducting barrier that blocks electrical contact between a cathode and an anode while allowing ions to pass through. The pores are structured to be interconnected, so that gas or liquid can pass from one side of the substrate to the other.

[0153] In one embodiment of the present invention, the porous substrate may be a porous polymer film containing a thermoplastic resin in order to provide a shutdown function. Here, the shutdown function refers to a function that prevents thermal runaway of the battery by blocking the movement of ions through the melting of the thermoplastic resin and closing the holes of the porous substrate when the battery temperature rises.

[0154] In one embodiment of the present invention, the thermoplastic resin used in the porous substrate may preferably be a thermoplastic resin with a temperature of less than 200°C. In addition, the thermoplastic resin may be used without particular limitation as long as it can be used as a substrate for a separator, for example, but may be polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalene, or a mixture of two or more of these, but is not limited thereto.

[0155] In one embodiment of the present invention, the porous substrate may be a polyolefin substrate.

[0156] In one embodiment of the present invention, the porous coating layer may comprise inorganic particles and further comprise a binder resin such that the inorganic particles have all or at least a portion of their surface coated by the binder resin. In this case, the inorganic particles are surface-bonded and / or point-bonded via the binder resin. For example, the inorganic particles and the binder resin in the porous coating layer may be included in a weight ratio of 95:5 to 50:50. The porous coating layer has a plurality of micropores inside, and these micropores are interconnected in a structure, and has the structural characteristics of a porous layer that allows gas or liquid to pass from one side to the other.

[0157] In one embodiment of the present invention, the porous coating layer may have a porous structure derived from pores resulting from the interstitial volume between inorganic particles. The size or porosity (ratio of pore volume) of the pores can be controlled according to the particle size and size distribution. Through this structure, resistance to metallic foreign substances present on the electrode is increased, and at the same time, shrinkage of the porous polyolefin substrate is suppressed, thereby enhancing the safety of the electrochemical device.

[0158] In one embodiment of the present invention, the porous coating layer comprises a plurality of nodes including a binder polymer covering at least a portion of the surface of the inorganic particles and the inorganic particles; and one or more filaments formed in a thread shape from the binder polymer of the nodes, wherein the filaments have a node connecting portion extending from the nodes to connect other nodes, and the node connecting portion may have a structure in which a plurality of filaments derived from the binder polymer intersect each other to form a three-dimensional network structure.

[0159] In one embodiment of the present invention, the porous coating layer may be formed through a Safety Reinforced Separator (SRS) manufacturing method, a Ceramic Coated Separator (CCS) manufacturing method, or other known manufacturing methods, but is not limited thereto.

[0160] In one embodiment of the present invention, the inorganic particles may be used without particular limitation as long as they are electrochemically stable. That is, the inorganic particles that can be used in the present invention are not particularly limited as long as they do not undergo oxidation and / or reduction reactions within the operating voltage range of the applied electrochemical device (e.g., 0 to 5 V based on Li / Li+). Non-limiting examples of such inorganic particles include BaTiO3, Pb(Zr,Ti)O3 (PZT), and Pb 1-x La x Zr 1-y Ti y O3(PLZT, 0 <x<1, 0<y<1), Pb(Mg 1 / 3 Nb 2 / 3 Examples include O3-PbTiO3 (PMN-PT), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC, and TiO2, and one or more of these may be included.

[0161] In one embodiment of the present invention, when a binder resin is included in the porous coating layer, the binder resin may include, for example, a polyvinylidene fluoride-based resin (PVdF-based resin). In one embodiment of the present invention, the PVdF-based resin may include one or more of a homopolymer of vinylidene fluoride (i.e., polyvinylidene fluoride), a copolymer with a monomer capable of copolymerizing with vinylidene fluoride, and a mixture thereof. In one embodiment of the present invention, the monomer may be, for example, a fluorinated monomer and / or a chlorinated monomer. Non-limiting examples of the fluorinated monomer include vinyl fluoride; trifluoroethylene (TrFE); chlorofluoroethylene (CTFE); 1,2-difluoroethylene; tetrafluoroethylene (TFE); and hexafluoropropylene (HFP). Perfluoro(alkylvinyl) ethers such as perfluoro(methylvinyl) ether (PMVE), perfluoro(ethylvinyl) ether (PEVE), and perfluoro(propylvinyl) ether (PPVE); perfluoro(1,3-dioxol); and perfluoro(2,2-dimethyl-1,3-dioxol) (PDD), etc., and one or more of these may be included.

[0162] In one embodiment of the present invention, the first porous coating layer and the second porous coating layer may have the same composition, but may be formed with different compositions as needed, and the present invention is not limited thereto.

[0163] In one embodiment of the present invention, the binder in the porous coating layer may be the same as or different from the binder of the insulating coating part, i.e., the first adhesive binder and / or the second adhesive binder, and may be selected independently thereof.

[0165] According to another aspect of the present invention, an electrochemical element in which the above-described electrode assembly is housed in a case may be provided.

[0166] In one embodiment of the present invention, the case may be one that is conventionally used as a battery case, and is not particularly limited in its external shape according to the use of the battery. For example, the case may be a cylindrical, prismatic, pouch, or coin type using a can.

[0167] Once the electrode assembly described above is completed, it can be housed in a case and sealed in a conventional manner to manufacture an electrochemical device, wherein the electrochemical device may be, for example, a lithium secondary battery.

[0169] Meanwhile, an adhesive insulating coating portion may be provided on the separator to improve adhesion between the separator and the electrode or to prevent short circuits between the electrodes. However, in this case, when an adhesive insulating coating portion is provided on the separator, the coating liquid may impregnate into the pores of the separator, blocking the pores and consequently causing a problem of reduced air permeability of the separator. Accordingly, according to one aspect of the present invention, it is preferable to laminate the separator after providing an insulating coating portion on the active material layer of the electrode in contact with the separator as described above.

[0170] According to one embodiment of the present invention, when the above-described coating solution is applied onto a separator, the coating solution is impregnated into the pores on the surface of the separator, thereby reducing the air permeability of the separator. Consequently, an air permeability time exceeding 200 seconds / 100 cc may occur, which may result in a problem where the separator cannot be used as a separator for an electrochemical device. Here, the air permeability may be a value measured using a Gullley Densometer according to the ASTM D726-94 standard. Specifically, the air permeability is measured as 1 inch of the separator under the pressure of 12.2 in H2O with 100 cc of air. 2 It can be measured as the time (in seconds) taken to pass through the cross-section, that is, the air passage time.

[0171] In an electrode assembly manufactured according to one embodiment of the present invention, the separator exhibits an air flow time of 200 seconds / 100 cc or less, specifically 150 seconds / 100 cc or less, or 100 seconds / 100 cc or less, but the present invention is not limited thereto.

[0172] Accordingly, according to another aspect of the present invention, a method for manufacturing the electrode assembly described above is provided.

[0173] A method for manufacturing an electrode assembly according to another aspect of the present invention is,

[0174] A step of preparing a current collector and an electrode having an active material layer on at least one surface of the current collector,

[0175] A step of forming an insulating coating portion comprising inorganic particles and a binder over the entire outer periphery of one surface of the active material layer, and

[0176] It includes the step of rolling after contacting a separator membrane to the surface on which the insulating coating portion is formed.

[0177] As described above, the electrode on which the insulating coating portion is formed may be at least one of an anode and a cathode.

[0178] In addition, the electrode assembly manufactured as described above may exhibit a wet adhesion strength of 1 to 20 gf / 20 mm between the electrode and the separator formed with the insulating coating.

[0180] The present invention will be described in more detail below through examples, but the following examples are intended to illustrate the invention and the scope of the invention is not limited thereto.

[0181] [Preparation of composition for insulating coating]

[0182] Example 1

[0183] Al2O3 (D as an inorganic particle in water (H2O) 5080 parts by weight of (500 nm) and 20 parts by weight of binder were added and stirred to prepare an insulating coating composition.

[0184] The above binder is a first adhesive binder with a Tg of 50℃ (acrylic-based, D 50 400 nm) and a second adhesive binder with a Tg of -20℃ (acrylic-based, D 50 A mixture of 200 nm and 8 nm in a weight ratio of 8:2 was used.

[0186] Example 2

[0187] An insulating coating composition was prepared according to the same method as in Example 1, except that the first adhesive binder was changed to an acrylic binder with a Tg of 70°C and the second adhesive binder was changed to an acrylic binder with a Tg of -40°C.

[0189] Comparative Example 1

[0190] An insulating coating composition was prepared according to the same method as in Example 1, except that a first adhesive binder with a Tg of 50°C was used alone as a binder.

[0192] Comparative Example 2

[0193] An insulating coating composition was prepared according to the same method as in Example 1, except that a second adhesive binder with a Tg of -20°C was used alone as a binder.

[0195] Comparative Example 3

[0196] An insulating coating composition was prepared according to the same method as in Example 1, except that the first adhesive binder was changed to an acrylic binder with a Tg of 40°C and the second adhesive binder was changed to an acrylic binder with a Tg of 30°C.

[0198] [Preparation Example 1. Preparation of Electrode Assembly]

[0199] An electrode assembly was manufactured as follows using the insulating coating composition prepared above.

[0200] First, the positive active material (LiNi 0.8 Mn 0.1 Co 0.1 O2), a conductive material (carbon black), a dispersant, and a binder resin (a mixture of PVDF-HFP and PVDF) were mixed with water in a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for the positive electrode active material layer with a concentration of 50 wt% of the components excluding water. Next, the slurry was applied to the surface of an aluminum thin film (thickness 10 μm) and dried to form a positive electrode active material layer (thickness 120 μm). Each of the insulating coating compositions prepared above was applied to the outer periphery of one side of the manufactured positive electrode active material layer and dried to produce a positive electrode equipped with an insulating coating portion (thickness 1 μm) formed around the entire outer periphery of the active material layer (the total area of ​​the insulating coating portion was 17% of the total area of ​​one side of the positive electrode active material layer).

[0201] Graphite (a blend of natural graphite and artificial graphite), a conductive material (carbon black), a dispersant, and a binder resin (a mixture of PVDF-HFP and PVDF) were mixed with water in a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for a negative electrode active material layer with a concentration of 50 wt% of the components excluding water. Next, the slurry was applied to the surface of a copper thin film (thickness 10 μm) and dried to manufacture a negative electrode having a negative electrode active material layer (thickness 120 μm).

[0202] An electrode assembly was prepared by positioning the above-mentioned positive and negative electrodes facing each other and interposing a polyethylene separator with a thickness of 16 μm and a porosity of 46 vol% between them.

[0204] [Adhesion Strength Evaluation]

[0205] For each electrode assembly manufactured above, the wet adhesion, dry adhesion, and peel strength were evaluated using the following method, and the results are shown in Table 1 below. Table 1 below also summarizes the glass transition temperature characteristics of the binder used to form the insulating coating.

[0207] Wet adhesion

[0208] After cutting the anode and separator prepared above into pieces 25 mm X 60 mm in size, they were pressurized at 60°C at a pressure of 6.5 MPa for 1 second using a heat press, then the anode and separator assembly was placed in a pouch-type case, and 1 g of an electrolyte with a composition in which 1 M LiPF6 was dissolved in a mixed solvent of 1,3-dioxolane:dimethoxymethane (DOL:DME 1:1 v / v) was injected, and an aging process and a degassing process were performed for 1 day.

[0209] Afterward, the anode and separator assembly was removed from the case, mounted on a UTM device (LLOYD Instrument LF Plus), and a force was applied at a measurement speed of 300 mm / min and 90° to measure the force required to separate the bonded surfaces.

[0211] Dry adhesion

[0212] After cutting the anode and separator prepared above into pieces 25 mm X 60 mm in size, they were pressed using a heat press at 60°C with a pressure of 6.5 MPa for 1 second, then mounted on a UTM device (LLOYD Instrument LF Plus) and a force was applied at a measurement speed of 300 mm / min and 180° to measure the force required to separate the bonded surfaces.

[0214] peel strength

[0215] The anode prepared above was cut to a size of 15 mm X 100 mm. Double-sided adhesive tape was attached to a glass plate, and the insulating coating portion and the surface of the active material layer of the prepared anode were attached to the adhesive tape. Subsequently, the end of the attached insulating coating portion was mounted on a UTM device (LLOYD Instrument LF Plus), and a force was applied at a measurement speed of 300 mm / min at 180° to measure the force required to peel off the insulating coating portion and the active material layer.

[0216] Binder composition Wet adhesion (gf / 20mm) Dry adhesion (gf / 25mm) Peeling strength (gf / 15 mm) Comparative Example 1 Tg 50℃ Type 1 0 0 0 Comparative Example 2 Tg -20℃ Type 1 0 0 30 Comparative Example 3 Tg 40℃ / Tg 30℃ two-type mixture 0 3 5 Example 1 Tg 50℃ / Tg -20℃ Type 2 Mixture 10 20 25 Example 2 Tg 70℃ / Tg -40℃ Type 2 mixture 8 5 15

[0217] As shown in the results of Table 1 above, it was confirmed that when the insulating coating portion is formed around the entire outer periphery of the anode active material layer, using two types of adhesive binders—a first adhesive binder with a Tg of 50°C or higher and a second adhesive binder with a Tg of 20°C or lower—wet adhesion strength in the range of 1 to 20 gf / 20 mm can be exhibited. In particular, in the case of Example 1, which utilized a glass transition temperature difference of 100°C or less, it was confirmed to be superior to Comparative Examples 1 to 3 not only in terms of wet adhesion strength but also in terms of dry adhesion strength and peel strength.

[0218] On the other hand, in the case of Comparative Example 3, which used two types of binders with different glass transition temperatures as binders for the insulating coating (using binders with glass transition temperatures of 40°C and 30°C, respectively), it was confirmed that the adhesion strength (peeling strength) of the insulating coating was inferior, and both wet adhesion strength and dry adhesion strength were inferior. In addition, in the case of Comparative Example 1, which used only one type of binder with a Tg of 50°C, the peeling strength, wet adhesion strength, and dry adhesion strength of the insulating coating were all inferior, and in the case of Comparative Example 2, which used only one type of binder with a Tg of -20°C, it was confirmed that while the adhesion strength of the insulating coating was strongly secured, the wet adhesion strength and dry adhesion strength were not secured. Through this, it was inferred that in the case of Comparative Example 2, the binder was impregnated between the inorganic particles to increase the adhesion strength of the insulating coating, whereas the surface adhesion strength of the insulating coating was not secured.

[0220] [Comparative Preparation Example 1. Preparation of Electrode Assembly]

[0221] The insulating coating composition of Example 1 prepared above was used, and the anode, cathode, and separator prepared in Preparation Example 1 were prepared in the same way.

[0222] However, without forming an insulating coating portion on the anode, the insulating coating composition of Example 1 was applied to one side of a separator (thickness 16 μm, porosity 46 vol%) in contact with the anode and dried to prepare a separator having an insulating coating portion on one side.

[0223] An electrode assembly was manufactured by laminating the anode, separator, and cathode so that the insulating coating portion of the prepared separator and the anode face each other.

[0224] It was confirmed that the electrode assembly prepared according to Comparative Manufacturing Example 1 cannot be used as an electrochemical device because the pores of the separator are drastically reduced. Specifically, as a result of evaluating the air permeability of a separator equipped with an insulating coating as follows, it was confirmed that the air permeation time of the separator exceeded 200 s / 100 cc.

[0226] Measurement of air permeability (air time)

[0227] Air permeability was measured using a Gullley Densometer according to ASTM D726-94 standards. Specifically, the air permeability was measured at 1 inch of the membrane under measurement when 100 cc of air entered under a pressure of 12.2 in H2O. 2 It was measured as the time (in seconds) taken to pass through the cross-section, that is, the air passage time.

[0229] Although the present invention has been described above with reference to the embodiments and drawings, those skilled in the art will be able to make various applications and modifications within the scope of the present invention based on the above content. Explanation of the symbols

[0230] 1: Electrode tab 10: The whole house 11: Electrode active material layer 20: Insulating coating part 30: Separator

Claims

Claim 1 An electrode assembly comprising an anode, a cathode, and a separator interposed between the anode and the cathode, wherein at least one of the anode and the cathode comprises a current collector; an active material layer formed on at least one surface of the current collector; and an insulating coating portion formed on the entire outer periphery of one surface of the active material layer; wherein the insulating coating portion comprises inorganic particles and a binder, and the binder comprises a first adhesive binder having a glass transition temperature (Tg) of 50°C or higher and a second adhesive binder having a glass transition temperature (Tg) of 20°C or lower, and wherein the wet adhesion strength between the anode or cathode equipped with the insulating coating portion and the separator is 1 to 20 gf / 20 mm. Claim 2 An electrode assembly according to claim 1, wherein at least one of the positive electrode and the negative electrode comprises: an active material layer on each of the two sides of the current collector; and an insulating coating portion formed on the entire outer periphery of one side of each of the active material layers. Claim 3 An electrode assembly according to claim 1, characterized in that the difference in glass transition temperature (Tg) between the first adhesive binder and the second adhesive binder is 100℃ or less. Claim 4 delete Claim 5 delete Claim 6 An insulating coating composition comprising inorganic particles and a binder, wherein the binder comprises a first adhesive binder having a glass transition temperature (Tg) of 50°C or higher and a second adhesive binder having a glass transition temperature (Tg) of 20°C or lower. Claim 7 An insulating coating composition according to claim 6, wherein the first adhesive binder comprises a water-based particulate binder. Claim 8 A composition for an insulating coating according to claim 7, wherein the first adhesive binder comprises a water-based particulate binder having a particle size of 250 nm or more. Claim 9 A composition for an insulating coating according to claim 6, wherein the second adhesive binder comprises a water-based particle binder, a solution-based binder, or a mixture thereof. Claim 10 An insulating coating composition according to claim 9, wherein the second adhesive binder comprises a water-based particulate binder having a particle size of 250 nm or less. Claim 11 An insulating coating composition according to claim 6, characterized in that the weight ratio of the first adhesive binder and the second adhesive binder is 1:9 to 9:

1. Claim 12 An insulating coating composition according to claim 6, characterized in that the weight ratio of the inorganic particles to the binder is 7:3 to 9:

1. Claim 13 An electrochemical device characterized by an electrode assembly according to any one of claims 1 to 3 being housed in a case. Claim 14 A method for manufacturing an electrode assembly comprising the steps of: preparing an electrode having a current collector and an active material layer on at least one surface of the current collector; forming an insulating coating portion comprising inorganic particles and a binder on the entire outer periphery of one surface of the active material layer; and rolling a separator after contacting the surface on which the insulating coating portion is formed, wherein the electrode is at least one of an anode and a cathode, the insulating coating portion comprises inorganic particles and a binder, and the binder comprises a first adhesive binder having a glass transition temperature (Tg) of 50°C or higher and a second adhesive binder having a glass transition temperature (Tg) of 20°C or lower, and wherein the wet adhesion strength between the electrode on which the insulating coating portion is formed and the separator is 1 to 20 gf / 20 mm.

Citation Information

Patent Citations

  • Composite binder for secondary battery, anode and lithium battery containing the binder

    KR1020140106301A

  • Secondary battery having stepped cell structure

    KR1020160046523A

  • Separator, Lithium battery containging Separator, and method for preparing Separator

    KR1020190004158A

  • Separator Comprising Binders Having Different Glass Transition Temperature and Method for Preparing the Same

    KR1020190083894A

  • A separator for a electrochemical device and a method for manufacturing the same

    KR1020210124087A